Sustainability analysis of biofuels through the supply chain using indicators - Teresa M. Mata (2013)
Although biofuels are seen as a viable option for partially replacing fossil fuels in the transportation sector, their widespread application raises questions about their potential economic, societal and environmental impacts. This article illustrates the application of a sustainability evaluation methodology to biofuels throughout their supply chain based on sustainability indicators. Five indicators (LCEE, FER, GW, LUI, and CSCE) were selected for the analysis, taking into account the information available in the open literature, and the availability of data to calculate them. Biodiesel and bioethanol from common feedstocks are compared with each other and with fossil diesel and gasoline, their main competitors, with the goal of identifying which ones are better from a sustainability point of view. Results show that ethanol from sugarcane is the most sustainable option, even when compared with dominant fossil fuels; while no feedstock for biodiesel production emerges as a better option. (c) 2013 Elsevier Ltd.